The Effect of Combination Alkaline Water and Iron Tablets on Improving Hemoglobin Level among Adolescent - Kiki Dwi Handayani; Melyana Nurul Widyawati; Ta’adi Ta’adi (Alta Dharma Publisher, 2020)
Anemia is one of the health problems in Indonesia. It was due to the suboptimal absorption of Fe and increased body acidity. Alkaline water is an alternative to improve hemoglobin levels since it can maximize the absorption of iron and balance the body's acid-base. The study aimed to examine the combination of alkaline water and iron tablets on Increasing the hemoglobin levels. A quasi-experimental study method with pre-test and post-test study with control group design. Forty-two samples were assigned to the intervention group and the control group. The intervention group received a combination of alkaline water with a pH of 9.5 as much as 1 liter and 60 mg iron tablets for 14 days. The control group received 60 mg of iron tablets. The assessment of hemoglobin levels was conducted before and after treatment. The results showed that the combination of alkaline water and iron tablets positively affected the Hb level among adolescents. The results showed that the variety of alkaline water and iron tablets positively affected adolescents' Hb levels. The alkaline water can be proposed as an innovation to increase hemoglobin levels. Further studies are expected to control the socio-cultural factor and food factor. Future researchers can develop studies related to alkaline water by adding other variables, namely blood pH and Malondialdehyde (MDA)